Perfectionism and Depression: Vulnerabilities Nurses Need to Understand - Sherri Melrose (Nursing Research and Practice)
Striving for excellence is an admirable goal. Adaptive or healthy perfectionism can drive ambition and lead to extraordinary accomplishments. High-achieving people often show signs of perfectionism. However, maladaptive, unhealthy, or neurotic perfectionism, where anything less than perfect is unacceptable, can leave individuals vulnerable to depression. In both personal and professional relationships, nurses need to understand how accepting only perfection in self and others is likely to lead to emotional distress. This paper reviews perfectionism as a personality style, comments on perfectionism and high achievement, discusses vulnerabilities to depression, identifies how to recognize perfectionists, and presents balancing strategies perfectionists can implement to lessen their vulnerability to depression.